2016
DOI: 10.5009/gnl14269
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Analysis of Proton Pump Inhibitor-Responsive Esophageal Eosinophilia in Korean Patients

Abstract: Background/AimsProton pump inhibitor-responsive esophageal eosinophilia (PPI-REE) is a newly recognized form of eosinophilic esophagitis (EoE) that responds to PPI therapy. It remains unclear whether PPI-REE represents a subphenotype of gastroesophageal reflux disease, a subphenotype of EoE, or its own distinct entity. The aim was to evaluate the clinicopathologic features of PPI-REE.MethodsSix patients were diagnosed with PPI-REE based on symptoms, endoscopic abnormalities, esophageal eosinophilia with ≥15 eo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 25 publications
1
7
0
Order By: Relevance
“…Since PPIs show few clinically important or serious side effects, they are widely used to treat the disease [35]. In Asian countries, cases of PPI-responsive esophageal eosinophilia have been reported to be around 50 % of the cases with esophageal eosinophilia [36][37][38][39]. In this study, 59 % of the cases responded to PPI administration, confirming previous reports from many countries.…”
Section: Discussionsupporting
confidence: 92%
“…Since PPIs show few clinically important or serious side effects, they are widely used to treat the disease [35]. In Asian countries, cases of PPI-responsive esophageal eosinophilia have been reported to be around 50 % of the cases with esophageal eosinophilia [36][37][38][39]. In this study, 59 % of the cases responded to PPI administration, confirming previous reports from many countries.…”
Section: Discussionsupporting
confidence: 92%
“…This recently recognized entity of esophageal eosinophilia is defined as PPI-responsive esophageal eosinophilia (PPI-REE) (6,7). Retrospective studies have demonstrated that 39 % to 71 % of children and adults with EEI have PPI-REE (13). At the moment, it is not clear whether it represents a part of EoE spectrum, GERD spectrum or a completely independent disease.…”
Section: Introductionmentioning
confidence: 99%
“…Tissue with a cobblestone-like appearance has been observed in patients with pathologic conditions of the esophagogastrointestinal tract, including those with eosinophilic esophagitis, H. pylori gastritis, gastric MALT lymphoma, and Crohn's disease ( 9 - 12 ). The new type of gastric lesion observed in this study is in line with these previous findings, indicating that gastritis, whether due to PPI use or other conditions, can induce a cobblestone-like appearance in gastric tissues.…”
Section: Discussionmentioning
confidence: 99%